Evaluation of the Qiagen 140-SNP forensic identification multiplex for massively parallel sequencing. (May 2017) - de la Puente, M.; Phillips, C.; Santos, C.; Fondevila, M.; Carracedo, Á.; Lareu, M.V.
Highlights: A new 140-SNP multiplex kit developed by Qiagen for massively parallel sequencing (MPS), applicable to both current MPS platforms was evaluated. Using Ion PGM™ system, sequence quality, genotype concordance and forensic sensitivity to mixtures or low-level DNA assessed. The Qiagen kit produced good quality sequence at high coverage and reliable genotypes. Full genotyping concordance in control DNA samples listed by 1000 Genomes and previously analyzed by SNaPshot or Ion PGM™ MPS. Low-level DNA requires careful sequence scrutiny in certain component SNPs. Abstract: A new forensic 140-SNP genotyping system from Qiagen, designed for massively parallel sequencing (MPS) analysis, was evaluated using the Ion PGM™ MPS system. Assessments consisted of the sequencing of: established control DNAs that had been previously genotyped with alternative PCR and library preparation kits supplied by Thermo Fisher Scientific for the Ion PGM™ system; a simple set of artificial DNA mixtures; DNA extracted from a degraded femur; and a dilution series to gauge forensic sensitivity. In addition to the reagents for the DNA target capture PCR and library preparation, Qiagen offer an alternative sequence analysis software system (Workbench), which was assessed alongside the Ion PGM™ Genotyper software for forensic MPS analysis. The Qiagen SNP genotyping system produced full genotyping concordance with previous data obtained with a similar SNP panel on the Ion PGM™ and in comparison to genotypes listed for 139 of the 140 SNPs in 1000 Genomes. The workbench software was as reliable as Genotyper in calling genotypes, although scrutiny of sequence data with IGV revealed the problem of sequence misalignment plagues a small proportion of the 140 SNPs in the Qiagen panel, a problem already recognized in multiple MPS studies of the same markers in alternative kits. The potential for genotype miscalls from sequence misalignment in certain SNPs will require manual inspection in cases where low-level or degraded DNA reduces the sequence coverage to a point where misalignment influences individual SNP genotype quality.